The Relation of Verbal and Non-Verbal Communication to Produce Meaning in the Movie - Royhan Naufaldi; Sri Wuli Fitriati; Suwandi Suwandi (Universitas Negeri Semarang, 2022)
Meaning in communication is crucial to be understood. Many problems appear due to misunderstandings between interlocutors in communication. Analyzing the speaker meaning in a communication is needed to avoid misunderstanding. There are aspects outside the literal meaning of communication that must be considered to avoid misunderstandings, they are verbal communication and non-verbal communication. This research conducted a qualitative method that use multimodal discourse analysis and focused on the relation of verbal and non-verbal communication to produce meaning. The theories that are used in this research were literal/explicit meaning and speaker/implicit meaning of Hurford et al. (2007), verbal communication of Jakobson (1985), and non-verbal communication of Moore et al. (2010). Moreover, there are presented theories of verbal and non-verbal communication that have been combined and developed by Kostić and Chadee (2014) and Tribus (2017). The source of data of the research was all of the characters in Harry Potter and the Sorcerer’s Stone the movie. Moreover, table instruments were used to collect and analyze the data. The findings showed that they are related to the shift of utterances’ forms, determine politeness, and reveal the implicit meaning of the speaker’s illocution. Therefore, it concluded that interlocutors must consider both verbal and non-verbal communication at the same time while having a conversation to deliver meaning successfully and to avoid misunderstanding. Thus, this research can enrich the theories of pragmatics and TEFL, especially for speaking purposes.